Post a New Question


posted by .

The sq root of -4 (3-sq root of -9)

a)6 +6i

Again the i's are in italics. I would think that c and d could be eliminated because the answer is suppose to be in the form a + bi but they could be trting to trick you.

I'm not quite sure what your problem is, so I'm going to assume it's something like the following:

√-4(3 - √-9)

i = √-1
i^2 = -1

Note: I'm using ^2 to mean squared.

√-4 = 2i
√-9 = 3i

Now we have: 2i(3 - 3i)


6i - 6i^2 =
6i - 6(-1) =
6i + 6
6 + 6i

I hope this helps and is what you were asking.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question